2003
DOI: 10.1093/hmg/ddg194
|View full text |Cite
|
Sign up to set email alerts
|

Insulator and silencer sequences in the imprinted region of human chromosome 11p15.5

Abstract: The imprinting of the genes on human chromosome 11p15.5 is thought to be controlled by two imprinting control regions located in two differentially methylated CpG islands upstream of the H19 gene (H19 DMR) and in intron 10 of the KCNQ1 gene (KvDMR). We have examined sequences in the human 11p15.5 genomic imprinted region for the presence of insulators and silencers using a position- and enhancer-dependent stable transfection assay. We have confirmed the existence of insulators in H19 DMR and discovered two nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 62 publications
4
52
1
Order By: Relevance
“…It has been reported that DMR-LIT1 are an orientation-independent silencer (Du et al, 2003;ManciniDiNardo et al, 2003;Thakur et al, 2003). Thakur et al (2003) proposed that a repressive chromatin structure established at DMR-LIT1 might propagate bidirectionally along the DNA to inactivate neighboring genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that DMR-LIT1 are an orientation-independent silencer (Du et al, 2003;ManciniDiNardo et al, 2003;Thakur et al, 2003). Thakur et al (2003) proposed that a repressive chromatin structure established at DMR-LIT1 might propagate bidirectionally along the DNA to inactivate neighboring genes.…”
Section: Discussionmentioning
confidence: 99%
“…H3K9 methylation was, however, barely detectable at CDKN1C promoter in the cancer cell lines and undetectable in cells with normal MI, suggesting that H3K9 methylation is not involved in CDKN1C repression on the paternal epigenotype chromosome. Since the human CDKN1C sequence was also reported to be an orientation-independent silencer (Du et al, 2003) and was not differentially methylated, CDKN1C may be synergistically repressed by the imprinting suppression and its own silencing activity on the paternal allele. In addition, methylated DMR-LIT1 on the maternal allele may function as a repressor of the CDKN1C silencer, leading to maternal expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its function as an ICR, targeted deletions of sequence spanning the DMD result in loss of both Igf2 and H19 imprinted expression (19,43,51,52). To date, the insulator model of imprinting control remains unique to the H19/ Igf2 locus, although other ICRs are expected to bind CTCF and/or exhibit insulator activity in vitro, including the KvDMR1 at the Kcnq1 locus (8,11,14).…”
mentioning
confidence: 99%
“…Consistent with its function as an ICR, targeted deletions of sequence spanning the DMD result in loss of both Igf2 and H19 imprinted expression (19,43,51,52). To date, the insulator model of imprinting control remains unique to the H19/ Igf2 locus, although other ICRs are expected to bind CTCF and/or exhibit insulator activity in vitro, including the KvDMR1 at the Kcnq1 locus (8,11,14).While targeted deletions of the DMD have suggested that at least three of the four CTCF binding sites are necessary for Igf2 and H19 imprinting (10, 51), DMD replacement alleles have been essential in validating the role of CTCF in regulating DMD function. The DMD replacement alleles with mutations that block CTCF binding perturb imprinting exclusively when maternally inherited: Igf2 becomes biallelically expressed due to loss of CTCF-dependent DMD insulator activity (31,41,47).…”
mentioning
confidence: 99%
“…Hence the presence of these specific repeats appears to be a hallmark of the IC2 region. Among the conserved motifs, we also found one copy of motif A2 in the chicken CpG island.In addition, we searched for consensus sequences of CTCF and YY1 binding sites (Bell and Felsenfeld 2000;Du et al 2003;Kim et al 2003) and other specific motifs of unknown function which were discussed as potential signatures of imprinting centers in the literature (Wang et al 2004). Based on consensus sequences, none of these motifs was found to be conserved in the putative mammalian IC2 CpG islands.…”
mentioning
confidence: 99%